Suppression of cirrhosis-related renal injury by N-acetyl cysteine - Narges Abdoli; Issa Sadeghian; Khadijeh Mousavi; Negar Azarpira; Mohammad Mehdi Ommati; Reza Heidari (Elsevier, 2020)
Cirrhosis-induced renal injury or cholemic nephropathy (CN) is a serious clinical complication with poor prognosis. CN could finally lead to renal failure and the need for organ transplantation. Unfortunately, there is no specific pharmacological intervention against CN to date. On the other hand, various studies mentioned the role of oxidative stress and mitochondrial impairment in the pathogenesis of CN. The current study aimed to evaluate the potential protective effects of NAC as a thiol-reducing agent and antioxidant in CN. Bile duct ligation (BDL) was used as a reliable animal model of cholestasis. BDL animals received NAC (0.25% and 1% w: v) in drinking water for 28 consecutive days. Finally, urine, blood, and kidney samples were collected and analyzed. Significant elevation in serum biomarkers of renal injury, along with urine markers of kidney damage, was evident in the BDL group. Moreover, markers of oxidative stress, including reactive oxygen species (ROS) formation, lipid peroxidation, protein carbonylation, and increased oxidized glutathione (GSSG) were evident detected in the kidney of cholestatic rats. Renal tissue antioxidant capacity and reduced glutathione (GSH) were also significantly depleted in the BDL group. Significant mitochondrial depolarization, depleted ATP content, and mitochondrial permeabilization was also detected in mitochondria isolated from the kidney of cholestatic animals. Renal histopathological alterations consisted of significant tissue fibrosis, interstitial inflammation, and tubular atrophy. It was found that NAC (0.25 and 1% in drinking water for 28 consecutive days) blunted histopathological changes, decreased markers of oxidative stress, and improved mitochondrial indices in the kidney of cirrhotic rats. Moreover, serum and urine biomarkers of renal injury were also mitigated in upon NAC treatment. These data indicate a potential renoprotective role for NAC in cholestasis. The effects of NAC on cellular redox state and mitochondrial function seem to play a fundamental role in its renoprotective effects during CN.